Nutrient limitation mediates soil microbial community structure and stability in forest restoration - Kang, Haibin; Xue, Yue; Cui, Yongxing; Moorhead, Daryl L.; Lambers, Hans; Wang, Dexiang (The Science of the total environment, 2024)
Soil microorganisms are often limited by nutrients, representing an important control of heterotrophic metabolic processes. However, how nutrient limitations relate to microbial community structure and stability remains unclear, which creates a knowledge gap to understanding microbial biogeography and community changes during forest restoration. Here, we combined an eco-enzymatic stoichiometry model and high-throughput DNA sequencing to assess the potential roles of nutrient limitation on microbial community structure, assembly, and stability along a forest restoration sequence in the Qinling Mountains, China. Results showed that nutrient limitations tended to decrease during the oak forest restoration. Carbon and phosphorus limitations enhanced community dissimilarity and significantly increased bacterial alpha diversity, but not fungal diversity. Stochastic assembly processes primarily structured both bacterial (average contribution of 74.73 % and 74.17 % in bulk and rhizosheath soils, respectively) and fungal (average contribution of 77.23 % and 72.04 % in bulk and rhizosheath soils, respectively) communities during forest restoration, with nutrient limitation also contributing to the importance of stochastic processes in the bacterial communities. The migration rate (m) for bacteria was 0.19 and 0.23, respectively in both bulk soil and rhizosheath soil, and was greater than that for the fungi (m was 1.19 and 1.41, respectively), indicating a stronger dispersal limitation for fungal communities. Finally, nutrient limitations significantly affected bacterial and fungal co-occurrence with more interconnections occurring among weakly nutrient-limited microbial taxa and nutrient limitations reducing community stability when nutrient availability changed during forest restoration. Our findings highlight the fundamental effects of nutrient limitations on microbial communities and their self-regulation under changing environmental resources. [Display omitted] •C and P limitations enhanced community dissimilarity and increased bacterial α diversity.•Increasing C and P limitations promoted the bacterial community stochastic processes.•Nutrient limitations weakened microbial community stability.